Staging Ghana : Artistry and Nationalism in State Dance Ensembles - Schauert, Paul W. (Book collections on Project MUSE., 2015)
The Ghana Dance Ensemble takes Ghana's national culture and interprets it in performance using authentic dance forms adapted for local or foreign audiences. Often, says Paul Schauert, the aims of the ensemble and the aims of the individual performers work in opposition. Schauert discusses the history of the dance troupe and its role in Ghana's post-independence nation-building strategy and illustrates how the nation's culture makes its way onto the stage. He argues that as dancers negotiate the terrain of what is or is not authentic, they also find ways to express their personal aspirations, discovering, within the framework of nationalism or collective identity, that there is considerable room to reform national ideals through individual virtuosity.